Wet markets in Southeast Asia and access to healthy diets - Hofman, Margot; Trevenen-Jones, Ann (Frontiers in Sustainability, 2024)
Hunger and malnutrition in all forms continues to rise in Africa and Asia. Urban and rural communities' diets in Southeast Asia (SEA) are increasingly unhealthy, with consumption influenced by affordability and convenience. The cost of a healthy diet is a major barrier to accessing healthy foods in SEA. Wet markets are key places in food environments where people buy and sell a variety of foods. They are especially important for food and nutrition insecure communities. This mini narrative review explores the role that wet markets, in SEA food environments, play in providing local communities with access to healthy foods. Fourteen peer-review papers, published in English between 2017-2022, were identified during screening and analysed according to six food environment domains. Findings highlight that convenient access to wet markets facilitates access to fruits and vegetables in peri urban and urban areas. Fresh foods, most notably fruits, were viewed as being more expensive than processed foods which in turn influenced purchasing behaviour.Divergent findings were presented in the identified papers regarding affordability of food in wet markets. Concerns about food quality and the use of chemicals and pesticides were raised. This review was constrained by several factors including the lack of consistent and meaningful definitions and typologies of the varied forms of wet markets. Looking ahead, better defined interpretations of wet markets can enhance the development and refinement of appropriate policies and actions and comparison of wet markets, in respect of access to diverse, healthy foods, vendor practices and consumer food choices.